2012
DOI: 10.12968/jpar.2012.4.6.318
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, paramedic informal coping strategies: a review of the literature

Abstract: Frontline ambulance staff have high rates of sickness absence; far greater than any other National Health Service worker. Reports suggest that many of these instances are attributable to stress, anxiety and depression. Indeed, studies have observed that occupational stress is significant within the Ambulance Service. While academics frequently associate the causative factor as being related to traumatic incident exposure, there is a small, growing trend of researchers who have found that daily hassles are equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
0
32
1
2
Order By: Relevance
“…While qualitative approaches have previously examined paramedic experiences of providing care for people who selfharm (Rees et al, 2017), to the authors' knowledge this study is the first to illuminate in depth the first-hand perspectives of ambulance staff in relation to attendance at a suicide, including interaction with bereaved families and individuals at the place of death. These qualitative insights therefore build on and extend existing knowledge to reveal how multiple and intense sources of strain and experiences of attending cumulative traumatic events such as suicides may contribute to the raised levels of mental health morbidity, distress, suicidality, and sickness absence among first responders seen in existing quantitative studies and survey data (Beaton et al, 1995;Clohessy and Ehlers, 1999;Alexander and Klein, 2001;Bennett et al, 2004;Mildenhall, 2012;Pitman et al, 2014;Kimbrel et al, 2016;Stanley et al, 2016;Milner et al, 2017;Jones et al, 2018;Vigil et al, 2019).…”
Section: Contribution To Current Understandingmentioning
confidence: 85%
See 1 more Smart Citation
“…While qualitative approaches have previously examined paramedic experiences of providing care for people who selfharm (Rees et al, 2017), to the authors' knowledge this study is the first to illuminate in depth the first-hand perspectives of ambulance staff in relation to attendance at a suicide, including interaction with bereaved families and individuals at the place of death. These qualitative insights therefore build on and extend existing knowledge to reveal how multiple and intense sources of strain and experiences of attending cumulative traumatic events such as suicides may contribute to the raised levels of mental health morbidity, distress, suicidality, and sickness absence among first responders seen in existing quantitative studies and survey data (Beaton et al, 1995;Clohessy and Ehlers, 1999;Alexander and Klein, 2001;Bennett et al, 2004;Mildenhall, 2012;Pitman et al, 2014;Kimbrel et al, 2016;Stanley et al, 2016;Milner et al, 2017;Jones et al, 2018;Vigil et al, 2019).…”
Section: Contribution To Current Understandingmentioning
confidence: 85%
“…Unsurprisingly, it has been known for some time that levels of sickness absence among ambulance staff are higher than among other groups of National Health Service (NHS) staff (Bennett et al, 2004) and indeed, five times the national average (NHS Information Centre for Health and Social Care, 2012). Work-related stress has been indicated as a potential reason (Mildenhall, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence indicates that frontline paramedics have one of the highest sickness absence rates 361 (Mildenhall 2012). So, while the attraction of a career in paramedic practice among study 362 participants seems to have been motivated by altruistic values, it would seem important to harness 363 and sustain this through clear role expectations and access to a supportive culture and structure.…”
Section: External Support 332mentioning
confidence: 98%
“…When trying to remedy stress among EMS, typical programmes like support groups, debriefing, and counselling are beneficial. However, the EMS culture is a more influential factor (Cydulka et al, 1997;Mildenhall, 2012). In a review of literature, most paramedics preferred to manage feelings of distress informally within their own work environment (Mildenhall, 2012).…”
Section: Improving Ems Culturementioning
confidence: 99%
“…However, the EMS culture is a more influential factor (Cydulka et al, 1997;Mildenhall, 2012). In a review of literature, most paramedics preferred to manage feelings of distress informally within their own work environment (Mildenhall, 2012). Likewise, findings from a 2016 UK study (Clompus and Albarran) reported that both formal and informal methods of support enhanced resilience; yet paramedics relied more heavily on peer networks to deal with everyday pressures as formal methods involving management and debriefing were less available.…”
Section: Improving Ems Culturementioning
confidence: 99%